2008
DOI: 10.1007/s10038-008-0311-1
|View full text |Cite
|
Sign up to set email alerts
|

Response to genetic manipulations of liver angiotensinogen in the physiological range

Abstract: Genetic variation in the human angiotensinogen gene (AGT) influences plasma AGT concentration and susceptibility to essential hypertension by a mechanism that remains to be clarified. When one or two additional copies of the gene were inserted by gene titration (by homologous recombination with gap-repair at the AGT locus), both plasma AGT and arterial pressure were elevated in the physiological range in the mouse. The causal dependency between plasma AGT and blood pressure and the relative contribution of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…It is possible that an increase in local AGT levels and altered renal blood flow response, both seen with NMOD status, are contributing to the salt sensitivity observed in our T2DM-HTN population. Recent studies support this explanation, demonstrating a relationship between higher plasma and urinary AGT levels and greater salt sensitivity (38,39). Additional studies are also warranted to determine whether blocking AGT levels via a pharmacological RAAS inhibitor improves the vascular dysfunction, altered renal blood flow response, and salt sensitivity in T2DM, similar to HTN (35).…”
Section: Figmentioning
confidence: 82%
“…It is possible that an increase in local AGT levels and altered renal blood flow response, both seen with NMOD status, are contributing to the salt sensitivity observed in our T2DM-HTN population. Recent studies support this explanation, demonstrating a relationship between higher plasma and urinary AGT levels and greater salt sensitivity (38,39). Additional studies are also warranted to determine whether blocking AGT levels via a pharmacological RAAS inhibitor improves the vascular dysfunction, altered renal blood flow response, and salt sensitivity in T2DM, similar to HTN (35).…”
Section: Figmentioning
confidence: 82%
“…20 The mice were allowed to recover for at least 1 week after surgery. Blood pressure, heart rate, and activity were monitored for 10 s every half an hour.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of repeated measurement of blood pressure was carried out using SAS software as described previously. 20 Blood pressure was analyzed for daytime and nighttime separately to reduce the effects caused by the heterogeneity in activity during the two periods. A previous study in our laboratory has shown a significant change in variances in the transitions from active to inactive states.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Our group developed a model of liver overexpression of mouse AGT using the albumin enhancer promoter; these animals were mildly hypertensive. 9 In addition, we recently demonstrated that overexpression of mouse AGT in PT also causes hypertension. 10 The above studies helped delineate the potential importance of systemic and renal AGT in controlling BP; however one question that has not been fully addressed is whether these two AGT systems can influence one another-that is, do they operate jointly or independently?…”
mentioning
confidence: 98%